2018
DOI: 10.1097/md.0000000000011270
|View full text |Cite
|
Sign up to set email alerts
|

Effect of knee joint function training on joint functional rehabilitation after knee replacement

Abstract: This retrospective study investigated the effect of knee joint function training (KJFT) on joint functional rehabilitation after knee replacement in Chinese patients with severe knee osteoarthritis (KOA).Eighty-six eligible patients with severe KOA were included. Of those, 43 patients in the intervention group received KJFT and educational program, while the other 43 patients received educational program only. Primary outcome was measured by the Western Ontario and McMaster Universities Arthritis Index (WOMAC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Nine of the included studies reported the effect of physiotherapy interventions on knee pain scores [ 24 , 26 , 28 , 29 , 31 , 32 , 39 , 40 , 43 ]. The random effect meta-analysis for pain at 12–13 weeks showed that physiotherapy interventions favoured the treatment group, SMD − 0.175 [95% CI − 0.416 to 0.067] (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine of the included studies reported the effect of physiotherapy interventions on knee pain scores [ 24 , 26 , 28 , 29 , 31 , 32 , 39 , 40 , 43 ]. The random effect meta-analysis for pain at 12–13 weeks showed that physiotherapy interventions favoured the treatment group, SMD − 0.175 [95% CI − 0.416 to 0.067] (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies reported functional activity in patients following physiotherapy interventions [ 24 , 26 , 29 , 31 33 , 36 , 37 , 39 , 40 ]. Random effect meta-analysis of four studies with 322 patients [ 24 , 26 , 31 , 39 ] showed that functional activity of participants who received physiotherapy interventions improved their functional performance, SMD − 0.166 [− 0.420 to 0.088] (Fig. 3 d).…”
Section: Resultsmentioning
confidence: 99%
“…Effect size (ES; Cohen’s d ) was calculated using pooled standard deviations [24]. A sample size of 30 participants per group had been computed a priori to discriminate moderate inter-group effects [14] at the study’s primary endpoint (14 weeks post-surgery) for its primary outcome (PF). Statistical significance was accepted at p < 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…The angle of the hip joint is defined as the angle  between the limb stem and the thigh, the angle of the knee joint is defined as the angle  between the thigh and the calf, and the angle of the ankle joint is defined as the angle  between the calf and the dorsum of the foot. Knee joint stretching and bending is the most commonly used rehabilitation exercise for patients with lower extremity paralysis in the hospital, so we used knee joint stretching and bending exercises as the basis of the first group of experimental actions [18]. The first group of experiments mainly studied the flexion and extension motion of the knee joint and analyzed the flexion and extension motion trend of hip joint and ankle joint.…”
Section: Experimental Action Specificationmentioning
confidence: 99%